2023
DOI: 10.1101/2023.12.20.572654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A subcortical switchboard for exploratory, exploitatory, and disengaged states

Mehran Ahmadlou,
Maryam Yasamin Shirazi,
Pan Zhang
et al.

Abstract: To survive in evolving environments with uncertain resources, animals need to dynamically adapt their behavior and exhibit flexibility in choosing appropriate behavioral strategies, for example, to exploit familiar choices, to explore and acquire novel information, or to disengage altogether. Previous studies have mainly investigated how forebrain regions represent choice costs and values as well as optimal decision strategies during explore/exploit trade-offs. However, the neural mechanisms by which the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…We have found that the striatum is an unlikely candidate, despite being a major projection target of the ACC, since the prediction-error signal is under-represented in ACC neurons projecting to the striatum. Other likely brain regions may include the locus coeruleus, which has been implicated in updating current strategies through norepinephrine signalling 17,18,68,69 , or the dorsal raphe nucleus, which promotes behavioural flexibility through serotonin and glutamate signalling 70,71 .…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the striatum is an unlikely candidate, despite being a major projection target of the ACC, since the prediction-error signal is under-represented in ACC neurons projecting to the striatum. Other likely brain regions may include the locus coeruleus, which has been implicated in updating current strategies through norepinephrine signalling 17,18,68,69 , or the dorsal raphe nucleus, which promotes behavioural flexibility through serotonin and glutamate signalling 70,71 .…”
Section: Discussionmentioning
confidence: 99%